Urban and rural differences in frequency of fruit, vegetable, and soft drink consumption among 6-9-year-old children from 19 countries from the WHO European region - Heinen, Mirjam M; Bel-Serrat, Silvia; Kelleher, Cecily C; Buoncristiano, Marta; Spinelli, Angela; Nardone, Paola; Milanović, Sanja Musić; Rito, Ana Isabel; Bosi, A Tülay Bağci; Gutiérrrez-González, Enrique; Pudule, Iveta; Abdrakhmanova, Shynar; et al. (Obesity reviews, 2021)
In order to address the paucity of evidence on the association between childhood eating habits and urbanization, this cross-sectional study describes urban-rural differences in frequency of fruit, vegetable, and soft drink consumption in 123,100 children aged 6-9 years from 19 countries participating in the fourth round (2015-2017) of the WHO European Childhood Obesity Surveillance Initiative (COSI). Children's parents/caregivers completed food-frequency questionnaires. A multivariate multilevel logistic regression analysis was performed and revealed wide variability among countries and within macroregions for all indicators. The percentage of children attending rural schools ranged from 3% in Turkey to 70% in Turkmenistan. The prevalence of less healthy eating habits was high, with between 30-80% and 30-90% children not eating fruit or vegetables daily, respectively, and up to 45% consuming soft drinks on >3 days a week. For less than one third of the countries, children attending rural schools had higher odds (OR-range: 1.1-2.1) for not eating fruit or vegetables daily or consuming soft drinks >3 days a week compared to children attending urban schools. For the remainder of the countries no significant associations were observed. Both population-based interventions and policy strategies are necessary to improve access to healthy foods and increase healthy eating behaviors among children.
Keywords: sycené nápoje; Cross-Sectional Studies; dieta; children; fruit; rural; urban; Fruit; vegetables; průzkumy a dotazníky; Světová zdravotnická organizace; ovoce; průřezové studie; Pediatric Obesity; World Health Organization; stravovací zvyklosti; dítě; soft drinks; Child; internacionalita; zelenina; Humans; Access to Healthy Foods; Surveys and Questionnaires; Feeding Behavior; Carbonated Beverages; Diet; Internationality; Vegetables; obezita dětí a dospívajících; lidé; dostupnost zdravé stravy